The Сadmium Telluride Thin Films for Flexible Solar Cell Received by Magnetron Dispersion Method - R.V. Zaitsev; G.S. Khrypunov; N.V. Veselova; M.V. Kirichenko; M.M. Kharchenko; L.V. Zaitseva (Журнал нано- та електронної фізики)
For the purpose of creation of thin-film photoelectric converters on the basis of sulfide and telluride of cadmium the pilot studies of process of magnetron dispersion on a direct current of telluride of cadmium and influence of the modes of magnetron dispersion on crystalline structure of films of CdTe are conducted. CdTe films for basic layers of sheet photoelectric converters on flexible polyimide substrate by the method of magnetron dispersion on a direct current are received for the first time. It is experimentally shown that "chloride" processing of the received layers of telluride of cadmium leads to transformation of metastable hexagonal modification of telluride of cadmium in stable cubic. At the same time at the expense of the eutectic recrystallization body height of the sizes of areas of a coherent dispelling much and decrease by 1,5 times of level of microstrains is observed.